Cystoscopic placement of transurethral stent in a fetus with urethral stenosis. (26th June 2014) - Ruano, R.; Yoshizaki, C. T.; Giron, A. M.; Srougi, M.; Zugaib, M.
ABSTRACT We report the case of a fetus with severe megabladder, displaying the 'keyhole' sign on ultrasound imaging, that underwent cystoscopy at 22 weeks' gestation. There was a familial history of mild urethral atresia. Fetal cystoscopy revealed congenital urethral atresia. A guide wire was advanced through the fetal urethra and a transurethral vesicoamniotic stent was placed successfully. The fetus was delivered at 36 weeks' gestation and postnatal cystoscopy confirmed the absence of posterior urethral valves or urethral atresia. The infant was 5 years old with normal renal function at the time of writing. We conclude that fetal cystoscopic placement of a transurethral stent for congenital urethral stenosis is feasible. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd